Konstruksi Sosial Masyarakat Kota Bengkulu terhadap Gaya Komunikasi Laki-laki Feminin - Tarmizi Nurhidayat, Tarmizi Nurhidayat; Alfarabi, Alfarabi; Neneng Cucu Marlina, Neneng Cucu Marlina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The phenomenon of feminine men's communication styles in society has resulted in changes in values ​​that have received attention. This research aims to determine the social construction and actions of the people of Bengkulu city towards feminine men's communication styles using Peter L. Berger and Thomas Luckmann's Social Reality Construction Theory which includes three dialectical moments, namely externalization, objectivation and internalization. The results of this research are divided into three dialectical moments. First, the moment of externalization of informants who have circles and those who do not have circles with feminine men tend to stigmatize the communication style of feminine men like women, and is considered deviant behavior which is feared that there will be sexual deviations such as LGBT. Second, the moment of objectification of informants who have a circle and who do not have a circle with feminine men see the communication style of feminine men as a character in which the traits, attitudes and behavior shown in the form of self-presentation such as gentle and graceful demeanor, less manly, so considered weak men. Third, the moment of internalization of informants who have circles and those who do not have circles with feminine men consider that feminine men are good, friendly, pleasant individuals, good public speaking, expressive, confident, and tend to be the center of attention. The social construction of communities that have or do not have circles with feminine men assesses the communication style of feminine men as the character, traits, attitudes and behavior shown by certain individuals as a form of self-presentation which is considered positive and also negative. The social behavior of people who have or do not have circles with feminine men are open and can accept the communication style of feminine men but still limit their social interactions, interactions and communication for fear of deviation.